Landasan Ontologis dan Kualifikasi Makrifat Ibn ‘Atâ’ Allâh al-Sakandarî - Ghozi Ghozi (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2016)
Employing qualitative approach, this article examines ontological foundation and qualification of the concept of ma‘rifah promulgated by Ibn ‘Ata’ Allâh al-Sakandarî. The concept of ma‘rifah of Ibn ‘Atâ’ Allâh deals with two things. The first is the spiritual condition of Sufi (the holy experience), i.e. an existential experience of a Sufi. The second is Sufi’s expressions in the form of symbols, gestures, and ta‘bîr (an expression born from spiritual experience). Ibn ‘Atâ’ Allâh itemized the latter category into two different conditions, namely in-consciousness condition and ecstasy (unconsciousness condition). The study finds that his concept of ma‘rifah can be ontologically categorized into three forms, namely spiritual experience, reflection of spiritual experience, and discourse of ma‘rifat Allâh. Within spiritual experience, a sâlik is immersed in witnessing (shuhûd) of God. This is the highest condition of ma‘rifah. In reflection of spiritual experience, a Sufi spontaneously and unconsciously expresses his/her thoughts due to the lavishness of unrestrained spiritual flavors. The discourse of ma‘rifat Allâh takes a safe position in the perspective of ordinary people by tying the ma‘rifah with sharî‘ah and morality (akhlâq). Borrowing Mehdi Heiri Yazdi’s terms, these there form are called mysticism, the language of mysticism, and meta-mysticism.